PENGARUH PROMOSI, PENILAIAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN DI MARKETPLACE SHOPEE PADA MAHASISWA DI JAKARTA - Ratih Ayu Sekarini; Lisa Putri Khairani; Wiwin; Hilma Farhani (Jurnal Ekonomi dan Industri, 2023)
The development of industry and technology is currently very advanced andindirectly encourages the emergence of various start-ups in Indonesia by seeing theincreasing needs of the community. This study aims to determine the analysis of promotion,and product assessment of purchasing decisions in the shopee marketplace for students inJakarta. With a sample size of 250 people. Sampling in this study using non-probabilitysampling with purposive sampling technique. For data processing is done with the PLS(partial Least Square) analysis technique with the help of smartPLS 4.0. Based on testing,the data results show that promotion and product assessment have a positive and significanteffect on purchasing decisions at the Shopee marketplace in Jakarta.